Experiences of pupils with severe special educational needs at special education institutions - Kairienė, Daiva; Geležinienė, Renata; Kaffemanienė, Irena; Melienė, Rita; Miltenienė, Lina; Tomėnienė, Laima (Special Education, 2019)
The article reveals the experiences of pupils with severe special educational needs (SEN) at special education institutions, which are analyzed in the context of inclusive education approach and research conducted in foreign countries data. The study follows qualitative research methodology. The data collected employing the semi-structured pupils’ individual interview method are presented. The study highlights pupils’ opinions on the opportunities and limitations of education at special and mainstream schools, their attitude to learning and discloses peculiarities of psychosocial environment at special schools.